Synthesis of Cl Doped g-C3N4 with Enhanced Photocatalytic Activity Under Visible Light - Wan1, J.; Hu2, S.Z.; Li2, F.Y.; Fan2, Z.P.; Wang3, F.; Zhang4, J. (Asian Journal of Chemistry, 2014)
Cl-doped g-C3N4 was prepared by a simple method using dicyandiamide and NH4Cl as precursors. X-ray diffraction, UV-visible spectroscopy, Fourier transform infrared spectra, scanning electron microscope and photoluminescence were used to characterize the prepared catalysts. The results indicated that the introduction of Cl decreased the band gap energy and increased the separation efficiency of photogenerated electrons and holes. The activities of Cl doped g-C3N4 catalysts were tested in the photocatalytic degradation of Rhodamine-B under visible light. The rate constant of Cl doped g-C3N4 was 3.5 times higher than that of neat g-C3N4. The possible mechanism was proposed.